Subsistence practices among earthwork builders: Phytolith evidence from archaeological sites in the southwest Amazonian interfluves. (December 2015) - Watling, Jennifer; Saunaluoma, Sanna; Pärssinen, Martti; Schaan, Denise
Abstract: The history of human–environment interactions and the role of agriculture among pre-Columbian populations of Amazonia has been a long-standing topic of debate, usually backed by scattered data. Although most archaeologists agree that Amazonia was inhabited by demographically dense and socio-politically complex societies during the millennium that preceded the European conquest, the vast forests of the terra firme (uplands) interfluves have only recently been studied for human impacts. In this article, we present the results of phytolith analyses from samples recovered from archaeological sites situated in the interfluves of Southwestern Amazonia, and discuss their implications for subsistence systems among terra firme populations in areas devoid of anthropogenic dark earths (ADEs). We conclude that a subsistence strategy based on a mixture of domesticated and wild plants was widespread in the region, and that maize, squash, and palms were particularly important resources. Highlights: We report the first evidence for pre-Columbian subsistence in terra firme regions of Riberalta, Bolivia, and Acre state, Brazil. Maize, squash, and palms were consumed by earthwork builders in Southwest Amazonia. Concomitant use of cultivated and wild resources was widespread/common in the region. Evidence of pre-Columbian domesticates, including maize, in terra firme environments without Amazonian Dark Earths.